2018
DOI: 10.1007/s10534-018-0086-6
|View full text |Cite
|
Sign up to set email alerts
|

A review of the design and modification of lactoferricins and their derivatives

Abstract: Lactoferricin (Lfcin), a multifunction short peptide with a length of 25 residues, is derived from the whey protein lactoferrin by acidic pepsin hydrolysis. It has potent nutritional enhancement, antimicrobial, anticancer, antiviral, antiparasitic, and anti-inflammatory activities. This review describes the research advantages of the above biological functions, with attention to the molecular design and modification of Lfcin. In this examination of design and modification studies, research on the identificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 86 publications
0
28
0
Order By: Relevance
“…Highly cationic and amphipathic peptide properties can be synthesized and designed via in silico creations. For example, some chemical groups, such as acetylation or amidation, are added into the natural peptides to increase the cationic properties and target cell specificity (162). Replacement of D-amino acids in an amphipathic peptide, KLALKLALKALKAAKLA-NH 2 , and a hydrophobic interaction can increase the membrane-disrupting effect on high negative surface charge bilayers, which then promotes peptide penetration into the inner membrane regions (163).…”
Section: Development Of Therapeutic Acpsmentioning
confidence: 99%
“…Highly cationic and amphipathic peptide properties can be synthesized and designed via in silico creations. For example, some chemical groups, such as acetylation or amidation, are added into the natural peptides to increase the cationic properties and target cell specificity (162). Replacement of D-amino acids in an amphipathic peptide, KLALKLALKALKAAKLA-NH 2 , and a hydrophobic interaction can increase the membrane-disrupting effect on high negative surface charge bilayers, which then promotes peptide penetration into the inner membrane regions (163).…”
Section: Development Of Therapeutic Acpsmentioning
confidence: 99%
“…9 To overcome these drawbacks, various strategies have been designed, such as (i) inclusion of non-natural amino acids, and (ii) conjugation with sugars, lipids, and proteins, and (iii) polyvalent peptide synthesis (dimers, tetramers, etc.). 10 Bovine lactoferricin (LfcinB: 17 FKCRRWQWRMKKLGAP-SITC-VRRAF 41 ) is a 25-amino acid peptide with antibacterial, antifungal, antiparasitic, antiviral, and antitumoral activity. [11][12][13][14][15][16] LfcinB-derived short peptides have exhibited higher antibacterial activity than LfcinB and Lactoferrin themselves.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14][15][16] LfcinB-derived short peptides have exhibited higher antibacterial activity than LfcinB and Lactoferrin themselves. 10,[17][18][19][20][21] Previous studies have shown that the inclusion of non-natural amino acids in some LfcinB-derived sequences improved their antibacterial activity 13,[17][18][19][20] Furthermore, dimeric and tetrameric peptides containing the RRWQWR motif exhibited higher antibacterial activity than Lactoferrin or LfcinB. In like manner, tetrameric and dimeric peptides containing 20 RRWQWR 25 or 17 FKARRWQWRMKKLGA 31 sequences exhibited higher antibacterial activity against E. coli strains than their monomeric peptide analogues.…”
Section: Introductionmentioning
confidence: 99%
“…The five antimicrobial peptides used in this study have been reported to inhibit the growth of various kinds of viruses including HIV, HSV-1, HSV-2, etc. [12–15, 20–22]. However there has been limited information about the inhibitory activity of these peptides against the swine-origin viruses.…”
Section: Discussionmentioning
confidence: 99%
“…Indolicidin, a natural 13-amino acid antimicrobial peptide isolated from bovine neutrophils, could directly kill HIV-1 [14]. Bovine lactoferricin derived from bovine lactoferrin has been reported to exert antiviral activity to fight against human cytomegalovirus (HCMV), herpes simplex virus type 1 (HSV-1), HSV-2, and adenovirus [15]. Other antimicrobial agents, such as human defensins which is a group of beta-sheet peptides, can inhibit enveloped viruses such as HSV-1 and HSV-2, HIV-1, vesicular stomatitis virus (VSV), influenza virus, and HCMV by directly inactivating viruses [16].…”
Section: Introductionmentioning
confidence: 99%